2022
DOI: 10.1186/s12934-022-01968-1
|View full text |Cite
|
Sign up to set email alerts
|

Mediating oxidative stress enhances α-ionone biosynthesis and strain robustness during process scaling up

Abstract: Background α-Ionone is highly valued in cosmetics and perfumery with a global usage of 100–1000 tons per year. Metabolic engineering by microbial fermentation offers a promising way to produce natural (R)-α-ionone in a cost-effective manner. Apart from optimizing the metabolic pathways, the approach is also highly dependent on generating a robust strain which retains productivity during the scale-up process. To our knowledge, no study has investigated strain robustness while increasing α-ionone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Next, we evaluated strain performance in 125 mL shaking flasks. We observed that mixing and oxygen supply had dramatic effects on the monoterpene yields, similar to a recent study on α-ionone biosynthesis . With the decrease of shaking speed from 300 to 100 rpm, the geraniol yield was increased by over 6-fold from 62 to 402 mg/L, in contrast, geranial production only increased by 86% (Figure A).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Next, we evaluated strain performance in 125 mL shaking flasks. We observed that mixing and oxygen supply had dramatic effects on the monoterpene yields, similar to a recent study on α-ionone biosynthesis . With the decrease of shaking speed from 300 to 100 rpm, the geraniol yield was increased by over 6-fold from 62 to 402 mg/L, in contrast, geranial production only increased by 86% (Figure A).…”
Section: Resultssupporting
confidence: 88%
“…This observation was similar to a recent study on α-ionone biosynthesis in E. coli in which lower mixing also led to high yield of α-ionone in flasks. 32 High mixing often leads to high supply of oxygen, which might induce the oxidation of geraniol to geranial. This hypothesis was supported by the results in Figure 5A.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation